1990
DOI: 10.1055/s-2007-1013985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Hypothermic Ventricular Fibrillation, Multi-Dose Blood Cardioplegia, and Single-Dose Bretschneider Cardioplegia in Coronary Surgery

Abstract: 37 patients undergoing coronary revascularization were randomly assigned to three protocols for intraoperative myocardial protection: hypothermic ventricular fibrillation (HF) (n = 13), multi-dose blood cardioplegia (BCP) (n = 12) and single-dose Bretschneider's crystalloid cardioplegia (CCP) (n = 12). As intraoperative markers of ischemic damage myocardial ultrastructure, ATP, and CP contents were determined in left ventricular biopsy specimens taken before and after cardiac arrest. Release of serum enzymes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Given the increased vulnerability of the conduction system to ischemia, myocardial enzyme elevation could be representative of ischemic damage and myocardial necrosis in the conduction system, without simultaneous infarction of the nearby myocardium 22 . However, its utility probably lies more in ruling out a perioperative myocardial infarction than in the diagnosis of conduction disturbances 13,14,16,23,30 . Hake and coworkers studied the utility of 2‐dimensional transesophageal echocardiography (TEE) in the diagnosis of conduction disturbances 16 .…”
Section: Diagnosis and Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the increased vulnerability of the conduction system to ischemia, myocardial enzyme elevation could be representative of ischemic damage and myocardial necrosis in the conduction system, without simultaneous infarction of the nearby myocardium 22 . However, its utility probably lies more in ruling out a perioperative myocardial infarction than in the diagnosis of conduction disturbances 13,14,16,23,30 . Hake and coworkers studied the utility of 2‐dimensional transesophageal echocardiography (TEE) in the diagnosis of conduction disturbances 16 .…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…Baerman and Gundry found that blood cardioplegia is associated with a higher incidence, 10,15 while Rousou and Beyersdorf found a protective effect of blood cardioplegia on postoperative conduction disturbances. 8,13 This discrepancy could be explained by the difference in temperatures of the cardioplegia solutions employed in these studies, with the first two studies using cold blood cardioplegia, and the latter two using warm blood cardioplegia. Cold cardioplegia is shown to be associated with higher rates of conduction disturbances.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Potassium cardioplegia with added magnesium has become the standard approach, which can either be diluted in a cell-free medium (crystalloid cardioplegia) or in oxygenated blood (blood cardioplegia). Blood cardioplegia seems to offer advantages over crystalloid cardioplegia both clinically and experimentally (1,4,8,12,15). However, it is not known whether this unphysiological concentration of potassium has any effects on red blood cell (RBC) or white blood cell (WBC) populations.…”
mentioning
confidence: 99%